Aplicação da estratégia de controle ótimo em sistemas de geração eólica conectado à rede elétrica - Lima, Adelson Menezes (Universidade Federal Rural do Semi-Árido, 2014)
Renewable energy has been essencial in power generation, among then, the wind energy arouses great attention because it is a renewable source with largely in connection with the electric power system. This connection has provided several problems to the electrical system due to electronic converters, wind variation, type of machinery. In order to reduce these problems, hybrid controllers(PI+LQR) and optimal controllers(LQR) in the inverters connected to the grid are evaluated. For the evaluation of controllers were developed mathematical models in order to perform and validate the simulations with PSIM software, the manufacturer Powersim Inc. version 9.1. The results indicate that the hybrid and optimal controllers achieved good performances when compared with a conventional type controller (PI)
Application of optimal control strategy in wind power generation systems connected to the grid
Keywords: Wind energy; Optimal control; Power converter; Wind energy; Power qualit; Energia eólica; Controle ótimo; Conversor de potência; Energia eólica; Qualidade de energia; ENGENHARIAS::ENGENHARIA ELETRICA